Digestibilidade da soja semi-integral extrusada para leitões na fase inicial - Thomaz, Maria Cristina [UNESP]; Silveira, Antonio Carlos [UNESP]; Kronka, Rodolfo Nascimento; Kronka, Sergio Nascimento; Budiño, Fábio Enrique Lemos (FapUNIFESP (SciELO), 2012)
Two assays were conducted to determine the coefficients of digestibility (CD) and the digestible nutrients (DN) of the extruded semi-whole soybean (Assay 1 conventional feeding and Assay 2 feeding for sows, starting at 109 days of pregnancy and during the lactation and for lactating piglets and in the initial phase, with rations without soybean meal). Each assay was divided into two phases (32 and 50 days of age). Eight piglets weaned at 25 days of age were used. Total feces collection method was used. The following variables were analyzed in feed and in feces: dry matter, crude protein, ether extract, crude fiber and gross energy. The following average values were obtained: CDDM 88.87%; CDCP 86.81%; CDEE 85.41%; CDCF 78.22%; CDGE 80.21% and CMDE 95.71%, which allowed the calculation of the digestible nutrients: DDM 81.28%; DP 34.49%; DEE 14.02%; DF 4.49%; DEa 4087.86 kcal/kg and MEa 3912.73 kcal/kg. The different coefficients of digestibility were not affected by the differential feeding for sows and piglets nor by the different ages of the animals. Moreover, the extruded semi-whole soybean presented good levels of DN, concerning mainly the digestible and metabolizable energy.
Digestibility of extruded semi-whole soybean for piglets in the initial phase
Keywords: Protein sources; Soybean; Swine; Animalia; Glycine max; Suidae